2020
DOI: 10.24926/jcotr.v27i1.2219
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Resilience for Puerto Rican College Students in Transition After Hurricane Maria

Abstract: The primary purpose of this study is to explore the impact of 2017 Hurricane Maria on Puerto Rican college students directly affected by the storm, including how institutions of higher education fostered resilience for displaced and non-displaced students transitioning to navigating college after the storm. Findings indicate that participants were greatly affected by Hurricane Maria, and community ties, along with logistical challenges, influenced their college experiences after the storm. Participants shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Relocation, or moving residents from disaster-prone areas to safer locations, is often necessary to reduce community risk Sivakumar, 2014). Rehabilitation focuses on restoring and repairing damaged infrastructure, while reconstruction aims to rebuild houses and public facilities destroyed by disasters, the importance of taking into account aspects such as environmental sustainability, disaster resilience, and community participation is also recognized in post-disaster development strategies (Shelton & Thompson, 2020;Van Kessel et al, 2015).…”
Section: Post-disaster Residential Developmentmentioning
confidence: 99%
“…Relocation, or moving residents from disaster-prone areas to safer locations, is often necessary to reduce community risk Sivakumar, 2014). Rehabilitation focuses on restoring and repairing damaged infrastructure, while reconstruction aims to rebuild houses and public facilities destroyed by disasters, the importance of taking into account aspects such as environmental sustainability, disaster resilience, and community participation is also recognized in post-disaster development strategies (Shelton & Thompson, 2020;Van Kessel et al, 2015).…”
Section: Post-disaster Residential Developmentmentioning
confidence: 99%
“…We furthermore understand the importance of relationality given contexts of campus racial climate and racial microaggressions (Solorzano et al, 2000), an increased "matriculation gap" underscored by lack of representation of youth of Color on campus (Eberle-Sudre et al, 2015), and opportunities to support students of Color given socioeconomic and racial diversity (Park et al, 2013). Specifically, in the context of college orientation, transition, and retention, Shelton and Thompson (2020) analyzed experiences of three Puerto Rican students after Hurricane Maria as the students navigated the transition to higher education. The authors examined how a higher-education institution "fostered resilience for displaced and non-displaced students transitioning to navigating college" (p. 1).…”
Section: Undergraduate Preservice Teachers Of Color and The Urgency Omentioning
confidence: 99%
“…This noting is in sharp juxtaposition to my earlier mention of myself as having 'doubt' about performing academically at a PwI, especially given the national conference presentation was specifically in a research strand, a space typically held for those with much longer academic careers behind them. The collective work of the research team provided Chauntel opportunities for academic affirmation, and a place of comfort (Shelton & Thompson, 2020). She notes, "I can relate to you guys and you guys can relate to me."…”
Section: Quilt Panel 2: Moving From Collaborators To Fammentioning
confidence: 99%
See 1 more Smart Citation
“…These dynamics halted student enrollment and left displaced students invisible in school computer systems, not just in international cases of displacement, but also in national and even within-state cases These circumstances meant that displaced students often went unclassified as a distinct social group from other students and their needs and backgrounds were unaccounted for in school. As examples, in Morrice's 2013 study, refugee professionals enrolled in university were classified as international students and, as a result of a separate classification for asylum-seekers, had to pay higher fee rates [56], and Shelton and Thompson [57] mentioned in their study of students displaced by Hurricane Maria that professions showed a lack of concern by not proactively acknowledging the hurricane in classes and the ways in which individual students were affected afterward. In other words, computer systems and their lack of ability to share educational identification and tracking information on displaced students had trickle-down effects on displaced students' participation in higher education; their experiences were homogenized with that of others', preventing students from bringing their whole selves to their learning and identity development.…”
Section: Identity Invisibilitymentioning
confidence: 99%